A comparative study on enhanced arsenic(V) and arsenic(III) removal by iron oxide and manganese oxide pillared clays from ground water. Issue 1 (March 2016) - Mishra, Trilochan; Mahato, Dipak Kumar
Graphical abstract: Highlights: Enhanced arsenic uptake by iron oxide and manganese oxide pillared materials in comparison to pure clay. Iron oxide nanopillars has higher affinity towards As(V) whereas manganese oxide has equal affinity towards both As(III) and As(V). High uptake of As(III) by manganese oxide pillared materials is explained with mechanism. Arsenic uptake remains nearly same even in presence of Fe 3+ and Cl − . Continuous use of adsorbent for ten batches proves the applicability of the material in field trial. Synergistic effect of surface active sites and high surface area associated with pillared clay acts as driving force for increased arsenic uptake. Abstract: Stable iron and manganese oxide pillared clays were synthesized with high surface area and studied as adsorbents for the first time towards As(III) and As(V) so as to understand the role of both oxide pillars for both As(III) and As(V) adsorption. Both the pillared clay materials showed high surface area (>260 m 2 /g) and thermal stability (up to 500 °C). Equilibrium studies were carried out at different concentration using three different materials at pH of 6 at 28 °C. For both As(III) and As(V) adsorption the uptake capacity of pillared materials is found to be many fold in comparison to the starting clay. Manganese oxide pillared material shows better affinity towards As(III) due to in situ oxidation to As(V). Synergistic effect of high surface area and presence of active manganese oxide pillars helps in enhanced uptake of total arsenic including substantial amount of As(III). Studies on mixed arsenic solution with mixed adsorbent proved to be much better than the individual adsorbent particularly for the contaminated water with substantial amount of As(III). Arsenic uptake in presence of Fe(III) and Cl − shows negligible decrease in the efficiency. Both the pillared material performed much better when subjected to actual contaminated water continuously for ten times. No leaching of arsenic was observed which confirms the possibility of using these materials in actual field trial for enhanced arsenic removal for contaminated water.